Does socio-economic inequality in infant mortality still exists in India? An analysis based on National Family Health Survey 2005-06 and 2015-16 - Pradeep Kumar; Ratna Patel; Shekhar Chauhan; Shobhit Srivastava; Ankur Khare; Kamlesh Kumar Patel (Elsevier, 2021)
Introduction: Despite impressive progress, socio-economic inequalities in infant mortality persist in India. Therefore, the study determines the change in percentage contribution of different factors to total economic inequalities for infant mortality in India from 2005-06 to 2015-16. Methods: The study used the National Family Health Survey to carve out the results. Descriptive, bivariate, and binary logistic regression were used. Further, Income-related inequality in infant mortality was quantified by the concentration index (CI) and the concentration curve (CC). The study used Wagstaff's decomposition analysis to decompose the concentration index. The effective sample size for the study was 51,555 for NFHS 2005-06 and 259,627 for 2015-16. Results: The study found that economic inequality in infant mortality has increased over the two survey periods. The value of the concentration index increased from −0.14 in 2005-06 to −0.18 in 2015-16. The increase in inequality in infant mortality is higher in rural India than in urban India. Mother's education and open defecation contributed half (52%) of the inequality in infant mortality during 2015-16. Conclusion: Recommendations concerning the WASH (Water, Sanitation, and Hygiene) actions should be emphasized. The focus should be on eradicating the practice of open defecation, construction of latrines, and safe disposal practice of feces. There is also a need to provide mass education regarding nutrition and health, along with focusing on the correlates that aim at improving female's education.